2019
DOI: 10.1101/848663
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Using single visits into integrated occupancy models to make the most of existing monitoring programs

Abstract: 24 1. A major challenge in applied ecology consists in integrating knowledge from 25 different datasets to produce robust ecological indicators. To estimate species distribution, 26 occupancy models are a flexible framework that can accommodate several datasets obtained 27 from different sampling methods. However, repeating visits at sampling sites is a prerequisite 28 for using standard occupancy models, which may limit their use. Under certain conditions, 29 detection/non-detection data collected during sing… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…We considered 4 sampling occasions 𝑗 with similar sampling effort for each monitoring program (winter, spring, summer, and autumn). We extended the observation process of the multispecies occupancy model of Rota et al (2016a) to integrate two datasets in the spirit of Lauret et al (2021).…”
Section: Observation Processmentioning
confidence: 99%
See 1 more Smart Citation
“…We considered 4 sampling occasions 𝑗 with similar sampling effort for each monitoring program (winter, spring, summer, and autumn). We extended the observation process of the multispecies occupancy model of Rota et al (2016a) to integrate two datasets in the spirit of Lauret et al (2021).…”
Section: Observation Processmentioning
confidence: 99%
“…To overcome data scarcity, several authors have suggested to combine multiple datasets into an integrated modelling framework (see Kéry & Royle (2020), Chapter 10, for a review). In that spirit, we previously developed a single-species integrated occupancy model to map the distribution of bottlenose dolphins over the Northwestern Mediterranean Sea (Lauret et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, when integrating multiple detection-nondetection data sources in an IOM, each data source has its own unique detection model defined by Equations 3 and 4 that are conditional on a shared latent occupancy process defined by Equations 1 and 2. This joint-likelihood approach enables explicit estimation of different covariate effects (and intercepts) on the detection processes of each data source (Miller et al, 2019;Lauret et al, 2021;Zulian et al, 2021). The spOccupancy function intPGOcc fits IOMs.…”
Section: Integrated Occupancy Models (Ioms)mentioning
confidence: 99%